2018
DOI: 10.1186/s12914-018-0167-1
|View full text |Cite
|
Sign up to set email alerts
|

Health expenditure, child and maternal mortality nexus: a comparative global analysis

Abstract: BackgroundThis paper provides empirical evidence on how the relationship between health expenditure and health outcomes varies across countries at different income levels.MethodHeterogeneity and cross-section dependence were controlled for in the panel data which consist of 161 countries over the period 1995–2014. Infant, under-five and maternal mortality along with life expectancy at birth were selected as health outcome measures. Cross-sectional augmented IPS unit root, panel autoregressive distributed lag, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 76 publications
8
37
2
Order By: Relevance
“…In the long run, PHE exacts a significant impact on life expectancy, as a 1% increase in PHE is consistent with a 0.01% increase in life expectancy. This complements the findings of Rana et al () and Nixon and Ulmann (). Per capita income also increases life expectancy, but insignificantly, in both time periods.…”
Section: Empirical Findings and Discussion Of Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In the long run, PHE exacts a significant impact on life expectancy, as a 1% increase in PHE is consistent with a 0.01% increase in life expectancy. This complements the findings of Rana et al () and Nixon and Ulmann (). Per capita income also increases life expectancy, but insignificantly, in both time periods.…”
Section: Empirical Findings and Discussion Of Resultssupporting
confidence: 91%
“…Most of the studies in the literature seem to confirm that PHE improves health status. For instance, see Rana, Alam, and Gow () for 161 countries, Ventelou and Abu‐Zaineh () for MENA, Dhrifi (, ) for 93 countries, Linden and Ray () for 34 OECD countries, Kato et al () for Uganda, Asgari and Badpa () for Iran, Barenberg, Basu, and Soylu () for India, Balan () for 25 EU countries, Rahman et al () for 15 countries, Ahmad and Hasan () for Malaysia, Jaba et al () for 175 countries, and Kim and Lane () for 17 OECD countries.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Some countries were almost similar in terms of the ASR DALY but were relatively different in terms of HE per capita or vice versa. Similar results were obtained in other studies [20][21][22][23].…”
Section: Discussionsupporting
confidence: 92%
“…However, these studies have varying results with different data sets and methods used especially for maternal mortality ratio [ 4 – 10 ]. As pointed out in a recent study [ 9 ], an investigation of this kind requires accounting for “unobserved heterogeneity”, a challenge that most existing literature fails to address. As a contribution to health economics literature, this study employs a quantile estimation method with a bootstrapping technique that controls for heterogeneous parameters across countries and quantiles (0.05,…, 0.95).…”
Section: Introductionmentioning
confidence: 99%
“…A study for seven (7) countries in the sub-Saharan region of Africa revealed that there exists a nexus between gender inequality, health expenditure, and maternal mortality for the study period [ 8 ]. The relationship between health expenditure and mortality (infant, under-5, and maternal) for the period 1995–2014 showed a significant relationship between health expenditure and child mortality [ 9 ]. However, an insignificant relationship was found between health expenditure and maternal mortality.…”
Section: Introductionmentioning
confidence: 99%